DETERMINAN PERILAKU MAHASISWA DENGAN MOTIVASI DONOR DARAH DI ASRAMA BIAK KOTA JAYAPURA - Sherly N.Mamoribo; Karel Batmanlusi (LPSDI Bina Patria, 2024)
Background: Motivation to donate blood to teenagers can be done if teenagers have good knowledge, attitudes, family support, support from health workers, support from dormitory administrators regarding this matter. Therefore, literacy about blood donation must be promoted so that teenagers are empowered as voluntary donors because blood is a fluid in the body which functions to transport oxygen needed by cells throughout the body, supply body tissues with nutrients, remove metabolic waste substances, regulate the immune system. Purpose: research is about knowledge, attitudes, actions, family support, support from dormitory administrators and support from health workers regarding blood donation. Method: The research method used is an analytical survey (cross-sectional study). The research was conducted at the Biak Dormitory in August-September 2023. The population was 72 people, sampling using the Slovin formula obtained 62 people. Simple random sampling technique (simple random sampling). Questionnaire research instrument. Data were analyzed using univariate analysis. Presented in table form after which it is narrated. Results: The results of the study were more males, 37 people (59.7%), late teens (18-25 years) as many as 53 people (85.5%), there were still those who did not want to donate blood, 42 people (67, 7%), lack of knowledge 42 people (67.7%), lack of preparedness 36 people (58.1%), good family support 32 people (51.6%), good support from health workers 44 people (71%), support There are less than 39 dormitory administrators (62.9%), and their motivation is good.